Behavioral and Psychological Consequences of Boundary Spanning Burnout for Customer Service Representatives - Singh, Jagdip; Goolsby, Jerry R.; Rhoads, Gary K. (Journal of Marketing Research, 1994)
Marketing boundary spanners—especially customer service representatives—are notably susceptible to burnout. The authors define the burnout construct and develop hypotheses to examine if burnout acts as a partial mediator between role stressors and key behavioral and psychological job outcomes. Responses from 377 customer service representatives reveal that burnout levels are high relative to other burnout-prone occupations (e.g., police, nursing) and that burnout has consistent, significant, and dysfunctional effects on their behavioral and psychological outcomes. Moreover, burnout mediates the negative effects of role stressors on job outcomes, whereas the positive effects of role stressors are unmediated.